Geostrategy at the EU’s South-Eastern Gate - I. Tózsa; J. Sallai (Управленческое консультирование)
The study presents the geostrategic causes of Asian and African migration to Europe since 2015. Illustrated with maps and technical border protection data, it presents the Hungarian government’s response measures and its effects, with particular regard to the Southeastern border region of the European Union and the Schengen border region. The study highlights the geostrategic significance of the global process affecting Europe.